Sonoelectrochemistry in acoustically emulsified media - Banks, C; Rees, N; Compton, R (2002)
The physical processes giving rise to sustained electrolytic currents within sono-emulsions are explored and shown to arise from: (i) the 'thinning' of the diffusion layer at the active electrode and in particular (ii) the release of dissolved material from the suspended phase within the diffusion layer. © 2002 Elsevier Science B.V. All rights reserved.